Anthropometric and physiological profile of adolescent basketball players - Pourloulakis, Aristidis; Zandes, Charisios (Acta Universitatis Carolinae. Kinanthropologica, 2010)
The purpose of the present study was to reveal the differences in physical fitness between trained adolescents (basketball players, with regular training of six 90 minute training sessions pro week) and untrained pubertal boys of the same age (16 years), through several physical fitness tests (Astrand's submaximal aerobic test to predict O2max, vertical and standing long jumps, grip strength test, sit and reach test, joint mobility of lower limbs, speed shuttle run test and skinfold measurements). The second aim was to compare the fitness level between adolescent basketball players with the same training program but living and training in urban and/or rural areas. Altogether 33 pubertal basketball players (BBP) and 33 untrained adolescents (UA) of the same age (16 years) participated in this study. Basketball players (BBP) were divided into urban (n= 17) a rural area (n= 16) subgroups. It had been found that BBP had higher values in aerobic capacity (O2max), in vertical and horizontal jump, in joint mobility and they attained lower percentages of body fat in comparison with the control group (UA). Between the two subgroups of BBP, urban BBP had higher values in body weight, joint mobility (sit and reach test) and absolute values of aerobic capacity (but not in relative values) in comparison with rural BBP subgroup. In summary, the results suggest that regularly training in adolescents, such as basketball as applied here, improves O2max, muscle power and flexibility, and cause a decrease of percentages of body fat, independently the effect of biological and bodily maturation.
Keywords: Statistics as Topic; Anthropometry; statistika jako téma; průřezové studie; Physical Fitness; tělesná výkonnost; svalová síla; Adolescent; basketbal; lidé; antropometrie; Vital Capacity; Muscle Strength; vitální kapacita; Humans; Range of Motion, Articular; rozsah kloubních pohybů; Respiratory Physiological Phenomena; Basketball; Cross-Sectional Studies; složení těla; Body Composition; tuková tkáň; mladiství; fyziologie dýchací soustavy; Adipose Tissue